Mechanical and Rheological Properties of Polyurethane Elastomers from Hydroxy-Terminated Polybutadiene and Isophorone Diisocyanate Used as Liners for Composite Propellants - Quagliano, J.; Wittemberg, V.; Gonzalez, J.; Bacigalupe, A. (Journal of Research Updates in Polymer Science, 2015)
In this contribution, we studied mechanical and rheological properties of liners based on hydroxy terminated polybutadiene (HTPB) loaded with titanium dioxide and cured with isophorone diisocyanate (IPDI) or toluene diisocyanate (TDI). A thixotropic agent (Thixin R) was added, and viscosity was measured as a function of curing time, leading to much lower viscosities and longer pot life values. Mechanical properties (tensile strength and elongation at break) were not significantly affected but viscosity was reduced at all tested concentrations. Loss modulus (G’’) and storage modulus (G’) were measured during cure time at three different temperatures (7, 25 and 60°C) with IPDI, and at 7 and 25°C for TDI. Both curves did not intersect during the cure period studied (120 minutes) for IPDI but did so for TDI at 25°C with the formulation having a thixotropic additive. These results suggested that liner formulations will flow if sprayed onto the inner surface of the rocket case before propellant is casted.